Diagnostic and Therapeutic Challenges of Dermatofibrosarcoma Protuberans (DFSP): Insights from Libyan Medical Practitioners - Aiesha Imbarek,; Magbula Kaziri,; Karima Alfitory,; Abdallah Juwid, (AlQalam Journal of Medical and Applied Sciences, 2026)
Dermatofibrosarcoma protuberans (DFSP) is an uncommon soft tissue tumor that poses significant diagnostic and management challenges. In resource-limited settings such as Libya, insufficient awareness and limited diagnostic facilities may contribute to frequent misdiagnosis and delayed treatment. This study aimed to assess healthcare professionals’ experience, diagnostic approaches, and management strategies for DFSP in Libya. A cross-sectional survey was conducted among 213 healthcare professionals, including dermatologists, surgeons, oncologists, pathologists, radiologists, and general practitioners from various regions of Libya. Data were collected using a standardized questionnaire covering demographic characteristics, experience with DFSP, diagnostic methods, treatment practices, perceived challenges, and recommendations for improvement. Among participants, 65.7% had previously encountered DFSP cases, and 79.8% reported familiarity with the disease. Misdiagnosis was common, with lipoma (39.9%), keloid (23.5%), and dermatofibroma (18.8%) being the most frequent initial incorrect diagnoses. Biopsy with histopathological examination was the primary diagnostic method (61.0%), while 43.2% routinely used immunohistochemistry (IHC), most commonly CD34 (37.6%). The majority of respondents (65.7%) believed that DFSP is often misdiagnosed in Libya. Preferred treatment modalities included wide local excision (56.3%) and Mohs micrographic surgery (23.5%). Major challenges identified were late diagnosis (46.9%), limited diagnostic resources (37.6%), and insufficient clinician awareness (32.9%). The most frequently suggested improvements were organizing training programs and workshops (70.4%) and enhancing diagnostic facilities (56.3%). Specialty and years of professional experience were significantly associated with disease familiarity and use of IHC (p < 0.05). This study highlights substantial diagnostic and management challenges related to DFSP in Libya, primarily due to limited awareness and inadequate diagnostic infrastructure. Targeted training initiatives, improved access to diagnostic tools, and the development of national management guidelines are essential to promote early diagnosis and optimal patient care.